A new ophthalmic formulation containing antiseptics and dexpanthenol: In vitro antimicrobial activity and effects on corneal and conjunctival epithelial cells. (December 2020) - Mencucci, Rita; Favuzza, Eleonora; Bottino, Paolo; Mazzantini, Costanza; Zanotto, Elisa; Pellegrini-Giampietro, Domenico E.; Landucci, Elisa
Abstract: Antibiotic resistance is increasing even in ocular pathogens, therefore the interest towards antiseptics in Ophthalmology is growing. The aim of this study was to analyze the in vitro antimicrobial efficacy and the in vitro effects of an ophthalmic formulation containing hexamidine diisethionate 0.05%, polyhexamethylene biguanide (PHMB) 0.0001% disodium edetate (EDTA) 0.01%, dexpanthenol 5% and polyvinyl alcohol 1.25% (Keratosept, Bruschettini, Genova, Italy) on cultured human corneal and conjunctival cells. The in vitro antimicrobial activity was tested on Staphylococcus aureus, Methicillin-Resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa, Streptococcus pneumoniae, Streptococcus pyogenes and Streptococcus mitis . For each microbial strain 10 μL of a 0.5 MacFarland standardized bacterial inoculum were incubated at 25 °C with 100 μL of ophthalmic solution for up to 6 h. After different periods of time, samples were inoculated on blood agar with 5% sheep blood. Moreover, a 0.5 MacFarland bacterial inoculum was seeded in triplicate on Mueller-Hinton Agar or on Mueller-Hinton Fastidious Agar; then a cellulose disc soaked with 50 μL of ophthalmic solution was applied on the surface of agar and plates were incubated for 18 h at 37 °C, in order to evaluate the inhibition of bacterial growth around the disc. Human corneal and conjunctival epithelial cells in vitro were incubated for 5, 10 and 15 min with Keratosept or its components. The cytotoxicity was assessed through the release of cytoplasmic enzyme lactate dehydrogenase (LDH) into the medium immediately after exposure to the drugs; the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay was performed to evaluate the metabolic cell activity. Our results show that Keratosept ophthalmic solution gave an average logarithmic (log) reduction of bacterial load of 2.14 ± 0.35 within 6 h of exposure (p-value < 0.05 versus control saline solution). On agar plates, all microbial strains, excluding P. Aeruginosa, showed an inhibition zone of growth around the Keratosept-soaked discs. Keratosept and its components after 5 and 10 min did not show any cytotoxic effect on cultured corneal and conjunctival cells, and only after 15 min a significant reduction of cell viability and an increase of cytotoxicity compared to control (vehicle) was seen; dexpanthenol 5% and polyvinyl alcohol accelerated the wounding of corneal cells in vitro. In conclusion, Keratosept showed good antimicrobial activity on the tested strains; the ophthalmic solution and its components were safe and non-toxic for the corneal and conjunctival epithelial cells for 5 and 10 min at the concentrations analyzed, and dexpanthenol 5% and polyvinyl alcohol promoted the wounding of corneal cells. Highlights: Topical antibiotic overuse increases microbial resistance. Therefore, the interest towards antiseptics is growing. Keratosept ophthalmic solution showed a good antimicrobial activity in vitro. Keratosept showed low toxicity on corneal and conjunctival epithelial cells.